2021
DOI: 10.1108/ejm-10-2019-0820
|View full text |Cite
|
Sign up to set email alerts
|

Negative online reviews, brand equity and emotional contagion

Abstract: Purpose Despite the growing consensus that consumers extensively use online reviews and that negative reviews can significantly damage brand equity, it remains uncertain whether negative online reviews that focus on different aspects of a service have a similar or differential effect on brand equity. This study aims to fill this gap and explores the mediating role of emotional contagion and what kind of response helps better deter their negative effect. Design/methodology/approach This research is conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
0
13
0
3
Order By: Relevance
“…Konuk [ 39 ] showed that customers' tendencies to share their feedback online increase when they are satisfied with the product or service. However, when a product or service disappoints the customer, he/she tends to share even more, to taint the company's image or to inform other customers [ 39 , 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…Konuk [ 39 ] showed that customers' tendencies to share their feedback online increase when they are satisfied with the product or service. However, when a product or service disappoints the customer, he/she tends to share even more, to taint the company's image or to inform other customers [ 39 , 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…Emotional contagion happens when people imagine themselves in others' situations (Ahmad & Guzmán., 2021). Additionally, Hatfield et al, (2018) defined emotional contagion as the tendency to automatically mimic and synchronize facial expressions, vocalizations, postures, and movements with those of another person and, consequently, to converge emotionally.…”
Section: Literature Review Emotional Contagion Definitionmentioning
confidence: 99%
“…Thus, these sites through electronic word of mouth can succeed in something and can also make it lose (Luo & Zhong, 2015). Studies on emotional contagion arising from online social network sites provide evidence of the spreading of happiness and emotion to other people through people's online status (Ahmad and Guzmán., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, their study used service quality instead of EC in conjunction with social compliance. Although EC plays a significant role in service quality, a recent study (Ahmad and Guzm an, 2021) indicates that EC is only prominent in some service quality situations. This fact coupled with previously mentioned finding of mediating effect (Zhao et al, 2010) suggests that service quality is a potential mediating variable that is not included in the present study.…”
Section: Theoretical Implicationsmentioning
confidence: 99%